PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PRODUK MIE BASAH YANG MENGANDUNG FORMALIN - Bernald Sihite; Ermanto Fahamsyah (Jurnal Hukum Adigama, 2020)
Wet noodles are foods that are consumed in Indonesia. The storage period of noodles is very short, so many noodle producers in Indonesia use food additives to make them more durable. formalin is a food additive that is prohibited from being added to food products, because it can damage health. This research is about the legal facts that occur against consumer protection against formal wet noodle products and the role of the government in preventing the manufacture and distribution of formalin wet noodles in Indonesia. Normative legal protection is regulated in UU NO. 8/1999 and UU NO. 7/1996. Strengthened by the Ministry of Health No. 722 / Menkes / Per / IX / 1988. The agency appointed by the government is BPOM as the supervisor and BPSK as the consumer dispute settlement, this study uses the legal facts of decision No.1603 / Pid.Sus / 2017 / PN / Bks. Where producers are found guilty of producing and circulating wet noodles containing formaldehyde. The results of this study prove that legal norms against the abuse of formalin in wet noodle products are very important in preventing the production and distribution of formalin wet noodles in the community